The Imposition of Sanctions For Delay Reporting of A Will Deed To The Center For The Will List - Alex Siswanto (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
Humans from birth are destined to have property attached to themselves to be used as a means of carrying out life. These assets can be traded, donated, pledged, or even given to the heirs when he dies. A person may make a will before a notary as a general official who can record the final will of the testator and keep the will and report it to the register of the will center. The main purpose of making a will is related to the distribution of the property of the testator to the beneficiary so that there will be no disputes regarding inheritance in the future. In making a will, the notary plays a very important role from pre-making to the opening of the will before the heirs or testament. However, sometimes a notary can be negligent of the provisions of reporting each month to the list of will centers. This study examines the concept of a will more deeply, and how the notary's responsibility for negligence in registering a will with a will center register. The formulation of the problem in this legal research is the concept of a will and the role of a notary in storing and reporting to the center of the will list, the second problem formulation is the provision of sanctions against a notary who is negligent in reporting a will to the center of the will register. The conclusion in this study is that a will is a form of legal action carried out by the heir regarding the final will which in this case is assisted by a notary as a public official who is authorized to assist the process of issuing a will and keeping a will, as well as other obligations attached to reporting to list of will centers regarding the presence or absence of a will. The legal consequences for a notary who are negligent in reporting the presence or absence of a will in the central will list system, the notary must be responsible and accountable for his actions. With regard to the type of sanctions, that in PERMENKUMHAM No. 60 of 2016 does not clearly regulate what sanctions are given to a notary if he is negligent in carrying out his duties, therefore the inherent sanctions refer to the provisions of the Notary Position Act and may be subject to civil sanctions